Pernikahan Childfree Perspektif Imam Al-Ghazali Dalam Kitab Ihya’ Ulumuddin - Nawawi, Ghufron; Miftahuddin , Abdul Hafidz (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
Marriage is not merely a contractual agreement but holds intrinsic religious value. Therefore, entering into a marital union is an honorable path ordained by Allah to fulfill biological needs as a divine blessing. One of the objectives of marriage is to preserve the biological relationship between man and woman, aimed at nurturing a sacred lineage. However, societal advancements and changing mindsets, particularly in countries like France, England, and the Netherlands, have led some individuals to perceive having children as an additional burden. Consequently, certain families choose not to have children, whether biological, adopted, or stepchildren, a lifestyle commonly referred to as